Historical study of the design of retorts for mineral oil production, with particular reference to the Scottish shale oil industry - Stewart, Daniel (The University of Edinburgh, 1943)
Natural petroleum products such as pitch, heavy residue oils, naphtha and gas obtained from ground seepages, were known to the ancient civilisations of Asia, but refined petroleum oils,lubricants and waxes did not become available in Europe and America until after 1859 when Col. E.L. Drake bored the world's first oil well at Oil Creek in Pennsylvania. Mineral oils were however in use in the West, although to a very limited extent, long before this date, the source being a variety of solid carbonaceous mineral substances which were found to yield oil on destructive distillation. British patent records show that bituminous coal was distilled for the production of oil (apart from its known yield of gas) as early as the year 1681 and the numerous patents which were taken out in the 18th and 19th centuries give some indication of the intensity of the search which was made for suitable raw materials and for methods of obtaining the liquid products therefrom. While the majority of the earlier British patents specified coal and associated minerals as the oil source, definite reference was not made to oil shales until 1841 when Count de Hompesh took out a patent on the production of oil from "bituminous schists". This patent and another by Du Buisson in 1845, protected in Britain the process which had already been patented in France by Selligue in 1838. The raw material specified by Se111gue was "bituminous schist" from the arrondissement of Autun in the Department of Saone et Loire. Shale oil had, however, been made from Autun "schists" by Laurent in the year 1835 and shale oil products were shown by Selligue and de la Haye at the Paris Exhibition of 1839. The shale oil industry, however, had its real beginning in Scotland in 1850 when Jas. Young was granted Patent No. 13292 on "Improvements in the treatment of certain bituminous mineral substances and in obtaining products therefrom" and when immediately thereafter he, in association with W. Meldrum and I.W. Binney, set up a plant at Bathgate, West Lothian, to carry out the process on a commercial scale. Actually Young's patent made no reference to oil shale, but specified "parrot coal, cannel coal and gas coal ", and for about ten years the locally occurring Boghead coal or Torbane mineral was extensively distilled in Scotland, and even exported to Germany and America for the same purpose. When the reserves of this mineral were almost exhausted, a substitute was found in the oil shales of the Lower Carboniferous strata of central Scotland and oil shale has been used almost exclusively in the Scottish industry from about 1860 to the present day. The earliest retorting plant was primitive in design and extremely wasteful in fuel, but following the establishment of an industry by Young, development in Scotland was rapid and continuous up to the beginning of the present century, and in more recent years established designs have had important modifications made to them. It is the purpose of the present investigation to make a study of the evolution of shale retort design in this country from the simple forms of the early days to the modern continuous retort designed for maximum yield of products at high throughput rates and with low fuel consumption.
An historical study of the design of retorts for mineral oil production, with particular reference to the Scottish shale oil industry